On Sum-free Sets of Natural Numbers (Resenhas do Instituto de Matemática e Estatística da Universidade de São Paulo, 2014)
We give a brief survey on sum-free subsets of the natural numbers, highlighting recent results which may shed light on some old and new open problems in this area of combinatorial number theory.